Violence and the materiality of power - Torsten Menge (18140284) (2019)
The issue of political violence is mostly absent from current debates about power. Many conceptions of power treat violence as wholly distinct from or even antithetical to power, or see it as a mere instrument whose effects are obvious and not in need of political analysis. In this paper, I explore what kind of ontology of power is necessary to properly take account of the various roles that violence can play in creating and maintaining power structures. I pursue this question by contrasting the views of Hannah Arendt and Michel Foucault. For Arendt, power is generated and maintained by communicative practices. She argues that power and violence are ‘opposites’ because violence can only destroy but not create these practices. In contrast, Foucault’s conception explicitly allows violence to play a constitutive role in generating power. I argue that while Arendt is right to insist that power and violence are not identical, it does not follow that violence cannot play any role in constituting power. Guided by Foucault’s approach, I formulate a non-dualist account of the relationship between power and violence that takes seriously the role that bodies, material things, and built infrastructures play in making social relations ‘more durable’ and constituting power. Other Information Published in: Critical Review of International Social and Political Philosophy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/13698230.2019.1700344